Tear fluid as a source of biomarkers for glaucoma - N. B. Chesnokova; T. A. Pavlenko; O. V. Beznos (Российский офтальмологический журнал)
Review presents the analysis of literature data about metabolic changes in tear fluid (TF) of patients with glaucoma. Data for mass-spectrometry of TF proteome, cytokine profile, neurotrophic factors, proteinases and their inhibitors, extracellular vesicles, miRNA, catecholamines, endothelins are presented. Changes of some of these metabolic parameters outpace clinical manifestation of glaucoma and thus may have prognostic value. TF composition vary depending on the glaucoma stage. The anti-glaucomatous therapy also has influence on the TF composition due to the preservatives in the hypotensive formulations and drug substances themselves via different pathways. TF analyses can be used for the personal therapy adjustment. Data concerning the difference of TF composition in primary open-angle glaucoma and pseudoexfoliative glaucoma confirm the difference of their pathogenesis. Pseudoexfoliative syndrome with glaucoma and without one are also characterized by different alternations in TF. The data presented confirm the diagnostic value of TF as a source of biomarkers for the prognosis of glaucoma development and for the personal therapy adjustment.